Analysis of Students' Initial Science Literacy Ability on Global Warming Materials - Fariz Muhammad Giftari; Navis Irvanan Niam; Diah Mulhayatiah; Muhammad Minan Chusni (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2022)
Physics is a science that is very much needed in the world of education because it helps students face the challenges of the 21st century. In facing the opportunities and challenges of the 21st century, everyone, especially students, needs two competencies, namely 21st-century skills and scientific literacy. Improving scientific literacy skills can increase Indonesia's PISA scores. This study aims to determine students' initial literacy skills related to science material studied in high school physics classes about global warming. The type of research used is descriptive research. Descriptive research aims to describe, analyze, capture, and explain the prevailing conditions. This is intended to describe the initial competence of scientific literacy about global warming. The results obtained by the average student response to global warming science literacy are in the "enough" category. The scientific literacy context dimension is smaller than the knowledge dimension.